2015
DOI: 10.3389/fpls.2015.00780
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and transcriptional expression analysis of mitogen-activated protein kinase and mitogen-activated protein kinase kinase genes in Capsicum annuum

Abstract: The tripartite mitogen-activated protein kinase (MAPK) signaling cascades have been implicated in plant growth, development, and environment adaptation, but a comprehensive understanding of MAPK signaling at genome-wide level is limited in Capsicum annuum. Herein, genome-wide identification and transcriptional expression analysis of MAPK and MAPK kinase (MAPKK) were performed in pepper. A total of 19 pepper MAPK (CaMAPKs) genes and five MAPKK (CaMAPKKs) genes were identified. Phylogenetic analysis indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 96 publications
(151 reference statements)
1
46
0
Order By: Relevance
“…Gene structure analysis could contribute to better understanding its functions, regulation, and evolution (Liu et al, 2015 ). In order to get some insight into the gene structure of BdMAPKKK genes, the exon/intron organization of them was analyzed (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gene structure analysis could contribute to better understanding its functions, regulation, and evolution (Liu et al, 2015 ). In order to get some insight into the gene structure of BdMAPKKK genes, the exon/intron organization of them was analyzed (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 108 sequences from potato, 63 from eggplant, 79 from pepper, and 64 from coffee have been reported in this study based on perfectly conserved signature motifs belonging to the three major families of the MAPK cascade. Although, few members of some of these families were reported recently ( Daigle & Matton, 2015 ; Kong et al, 2012 ; Lazar et al, 2014 ; Liu et al, 2015 ; Mohanta et al, 2015 ; Wu et al, 2014 ), this articles reports the largest set of genes identified from all three of these gene families and their further subfamilies in the said species. Phylogenetic analysis of the reported sequences shows the conservation of the genes throughout the Solanaceae plant family and coffee, which is closely related to Solanaceae species in terms of its genetic make-up.…”
Section: Resultsmentioning
confidence: 89%
“…Identification of the three complete families of the MAPK cascade has not been done earlier in potato, eggplant, pepper, and coffee. However, being widely studied due to their vital functions, a few of these genes have recently been identified and reported as MPK, MKK, and MAPKKK in tomato ( Daigle & Matton, 2015 ; Kong et al, 2012 ; Lazar et al, 2014 ; Mohanta et al, 2015 ; Wu et al, 2014 ); as MPK, MKK, and MEKK-like from MAPKKK in potato ( Daigle & Matton, 2015 ; Lazar et al, 2014 ; Mohanta et al, 2015 ); and, as MPK and MKK in pepper ( Liu et al, 2015 ). However, genome identification of the three complete gene families hasn’t been reported for any one of them; thus, such an identification will be a huge step forward towards unraveling their functionality and importance.…”
Section: Resultsmentioning
confidence: 99%
“…rapa ; these genes were divided into four groups as in A . thaliana , rice, and other plant species [ 3 , 11 , 33 , 34 ]. The use of a pair of near isogenic lines, CR BJN3-2 and CS BJN3-2, allowed us to identify the probable BraMKK and BrMPK genes participating in B .…”
Section: Discussionmentioning
confidence: 99%